Synthesis, Characterization and Evaluation of Supercapacitive Response of Dodecylbenzenesulphonic Acid (DBSA) Doped Polypyrrole/Zirconium Dioxide Composites - Rizwan Ullah (MDPI AG, 2021)
An in-situ chemical oxidative method was used to effectively synthesize a promising supercapacitor material based on PPy/ZrO2 composites. The synthesized materials were characterized by different analytical techniques, such as UV/visible (UV/Vis) spectroscopy, Fourier-transform infra-red spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and scanning electron microscopy (SEM). The inclusion of ZrO2 into the PPy matrix was verified by vibrational spectra and structural analyses. The (TGA) results showed that incorporating ZrO2 into the polymeric matrix improved its thermal stability. In addition, the electrochemical properties of the synthesizedmaterials were investigated byusing cyclic voltammetry (CV) and galvanostatic charge/discharge (GCD). The PPy/ZrO2 composite demonstrated excellent super capacitive performance, and high specific capacity of 337.83 F/g, with an exceedingly high energy density of 187.68 Wh/kg at a power density of 1000 W/kg. The composite materials maintain good stability after 1000 charge and discharge cycles, with 85% capacitance retention. The PPy/ZrO2 possesses a high capacitance, an attractive micro-morphology, and a simple synthesis method. The findings indicate that the PPy/ZrO2 composite could be a promising electrode material for high-performance supercapacitor applications.